3(x+12)=6

Simple and best practice solution for 3(x+12)=6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(x+12)=6 equation:


Simplifying
3(x + 12) = 6

Reorder the terms:
3(12 + x) = 6
(12 * 3 + x * 3) = 6
(36 + 3x) = 6

Solving
36 + 3x = 6

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-36' to each side of the equation.
36 + -36 + 3x = 6 + -36

Combine like terms: 36 + -36 = 0
0 + 3x = 6 + -36
3x = 6 + -36

Combine like terms: 6 + -36 = -30
3x = -30

Divide each side by '3'.
x = -10

Simplifying
x = -10

See similar equations:

| -5(6m+5)=-25-3m | | 8x+11+3x=13-7x+4 | | 4h-I+3h-5i+h= | | -12(x+3)+4(4x-3)=3(x-6)+14 | | 16=4w+9 | | -11+5n=-91 | | 5(-7b-7)= | | X-10=2x+4 | | d-14.25=23.5 | | 8+3b=-1+3(3+b) | | 3/4-1+1/2x=3/8x+1/4 | | 2x-3+x=3x+1 | | -3(x-1)=2x+48 | | 5(x-7)+x=6(x-7)+7 | | x^2-16x=.35 | | 5(x-1)2x=2x-5 | | -7y+26=-3(y-6) | | X+11+x+14=17 | | 6n-3n+3120=5400 | | 8(-5b+7)+4b= | | 1250=50+30x | | p-49=5(p+3) | | -30-5n=-6(n+4) | | -135/-9=15 | | 10(s-6)=-149 | | 8x+11+3=23-7x+4 | | 5(v-3)=-9v-29 | | 44c+49=457c-7 | | 8(X-1)=-2x+52 | | 9(x+1.4)=18 | | -3(6x-8)+7=-18+31 | | 2(x+7)+6=2x+2 |

Equations solver categories